Review of the Formulating of the Code of Conduct in South China Sea between ASEAN and the People's Republic of China - Farhan Muhammad Aditomo; Edy Prasetyono (Budapest International Research and Critics University, 2022)
This paper discusses about ASEAN and the People's Republic of China (PRC)'s resolution attempts in the South China Sea (SCS) dispute. This paper discusses the process of conflict resolution between ASEAN and the People's Republic of China (PRC) in the South China Sea (SCS) dispute issue since the declaration of conduct and its following moves were not yet able to formulate the planned code of ethics. This study aims to find out the causes of slow development of the COC of the South China Sea. This research uses qualitative methods to gather both primary and the secondary sources. Regime theory by Krasner is used by this research to see what factors cause both parties to be unable to formulate a code of ethics in the South China Sea. The conclusion from this research is the COC's development as a security regime in the South China Sea.